Chitosan-functionalized PLGA Nanoparticles: Exploring Recent Patents, Advanced Strategies for Controlled and Targeted Anticancer Therapy - Madhusudan Maity; Niranjan Panda; Subas Chandra Dinda; Bikash Ranjan Jena; Parameswar Patra; Chinmaya Keshari Sahoo (Recent Patents on Nanotechnology, 2026)
Introduction: Recent advances in the field of nanotechnology have accelerated the development of polymeric nanocarriers for cancer therapy, enabling high precision and improved therapeutic efficiency. Among these, poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) have gained significant attention, as PLGA is a U.S. FDA-approved polymer for various biomedical applications. Methods: PLGA has several important properties, including biodegradability, biocompatibility, sustained drug-release properties, and minimal toxicity. However, mucoadhesion and cellular uptake of the delivery system in the tumour microenvironment are slightly compromised due to the negative surface charge of the PLGA. This issue can be overcome by surface functionalization with chitosan (CS), a cationic polysaccharide. This helps to improve nanoparticle stability, permeability, and sitespecific targeting. This also enables targeted delivery of the drug to the tumor's microenvironment. Results: This review provides a comprehensive overview of the chemical composition and key properties of PLGA, the characteristics of chitosan, and the rationale for chitosan surface functionalization. Additionally, it discusses various fabrication methods of the NPs, including emulsification, nanoprecipitation, salting-out, dialysis, spray drying, and microfluidics techniques. Discussion: The characterization studies included determination of particle size, zeta potential, and morphology, which confirm the successful chitosan coating. In vitro and in vivo studies further demonstrated the potential of this nanoparticle system for controlled, targeted, and biocompatible delivery of anticancer agents. Conclusion: This review also provides a comprehensive roadmap of current challenges and future perspectives along with a survey of recent patents related to this delivery system.